Integrating Supply Chain Risk Management and Organizational Agility in Post-pandemic Era: A Pathway to Superior MSMEs Performance in Indonesia - Fauzan, Tribowo Rachmat; Syara, Ajeung Syilva (Transpublika Publisher, 2025)
SMEs, being crucial contributors to economic growth, often face significant supply chain risks that can impede their performance. The ability to manage these risks effectively in the post-pandemic era and to adapt swiftly to environmental changes (organizational agility) is vital for their success. This study explores the association between supply chain risk management (SCRM) and organizational agility (OA) in enhancing the performance of micro, small, and medium-sized enterprises (MSMEs) in Indonesia. Using a quantitative approach, data were collected from 254 Indonesian MSMEs across various industries through structured questionnaires. The analysis, conducted using structural equation modeling, reveals that both SCRM and OA have a significant positive impact on MSME's performance. The study findings suggest that Indonesian MSMEs that integrate robust risk management practices with agile organizational structures are better equipped to maintain operational efficiency and drive innovation. The study underscores the importance of SCRM and OA as strategic tools for MSMEs to enhance their competitiveness and resilience in a volatile market landscape. The results provide valuable insights for MSME managers and policymakers aiming to foster sustainable business practices and long-term growth.